Ability of Serum C-Reactive Protein Concentrations to Predict Complications After Laparoscopy-Assisted Gastrectomy: A Prospective Cohort Study. Issue 21 (May 2016) - Zhang, Kecheng; Xi, Hongqing; Wu, Xiaosong; Cui, Jianxin; Bian, Shibo; Ma, Liangang; Li, Jiyang; Wang, Ning; Wei, Bo; Chen, Lin
Abstract : Abstract: Inflammatory markers, including C-reactive protein (CRP) and white blood cell (WBC), are widely available in clinical practice. However, their predictive roles for infectious complications following laparoscopy-assisted gastrectomy (LAG) have not been investigated. Our aim was to investigate the diagnostic accuracy of CRP concentrations and WBC counts for early detection of infectious complications following LAG and to construct a nomogram for clinical decision-making. The clinical data of consecutive patients who underwent LAG with curative intent between December 2013 and March 2015 were prospectively collected. Postoperative complications were recorded according to the Clavien–Dindo classification. The diagnostic value of CRP concentrations and WBC counts was evaluated by area under the curve of receiver-operating characteristic curves. Optimal cutoff values were determined by Youden index. Univariate and multivariate logistic regression analyses were performed to identify risk factors for complications, after which a nomogram was constructed. Twenty-nine of 278 patients (10.4%) who successfully underwent LAG developed major complications (grade ≥III). CRP concentration on postoperative day 3 (POD 3) and WBC count on POD 7 had the highest diagnostic accuracy for major complications with an area under the curve value of 0.86 (95% confidence interval [CI], 0.79–0.92] and 0.68 (95% CI, 0.56–0.79) respectively. An optimal cutoff value of 172.0 mg/L was identified for CRP, yielding a sensitivity of 0.79 (95% CI, 0.60–0.92) and specificity 0.74 (95% CI, 0.68–0.80). Multivariate analysis identified POD3 CRP concentrations ≥172.0 mg/L, Eastern Cooperative Oncology Group Performance Status ≥1, presence of preoperative comorbidity, and operation time ≥240 min as risk factors for major complications after LAG. The optimal cut-off value of CRP on POD3 to predict complications following LAG was 172.0 mg/L and a CRP-based nomogram may contribute to early detection of complications after LAG.